PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI RSUD DR. RM. DJOELHAM BINJAI - Delimayani; Aisyah; Juliati; Nurlina (Jurnal Keperawatan Priority, 2023)
Service quality is a measure of how well the level of service provided is able to match customer expectations. Patient satisfaction is an evaluation or assessment after using a service, that the selected service at least meets or exceeds expectations. This type of research is a descriptive study using a cross sectional analytic study design. The research objective is to determine the effect of service quality on patient satisfaction at the Dr. General Hospital. RM. Djoelham Binjai. In this study, the sampling technique was carried out using a saturated sample technique of 75 people. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000< 0.05) then H0 is rejected so it can be concluded that there is an effect of service quality on patient satisfaction at the Dr. RM. Djoelham Binjai in 2021. The results of this study are expected to provide input to the hospital management to further improve the quality of service in order to increase patient satisfaction.